Fathoming the interaction between secondary metabolites of phylogenetically related Bacillus species and the plant metabolome. - Carrégalo Ríos, María Luisa; Molina-Santiago, Carlos; Berlanga-Clavero, María Victoria; Pineda-Dorado, M.; Barón Ayala, M.; Dorrestein, Pieter; De-Vicente-Moreno, Antonio; Romero-Hinojosa, Diego Francisco (My University, 2024)
Plant-beneficial microbes are known to provide multifaceted traits that contribute to plant health. Bacillus species, frequently found within the plant holobiont, are known to enhance seed germination, promote plant growth, and bolster defense mechanisms against phytopathogens[1], although the molecular shifts underlying these processes remain unstudied. Previous data has shed light on the topic, concluding that seed treatments lead to metabolic changes in adult plants. In this process the extracellular matrix component of Bacillus subtilis, TasA, and fengycin, a secondary metabolite, play crucial roles[2]. In this study, we hypothesize that this metabolic reprogramming at the seed level is conserved among closely related Bacillus species, while differences may arise from variations in secondary metabolite production. To evaluate this, we conducted an in-depth analysis of the metabolic profile of whole plants emerging from seeds treated with either Bacillus subtilis or Bacillus velezensis. We also analyzed the role of bacillomycin, a secondary metabolite mainly produced by the latter. We describe the different metabolomic patterns found in different parts of the plant, focusing specifically on leaves and stem sections, identifying tryptophan and alkaloids, in the case of B. subtilis, and a shift in the pool of lipids, for B. velezensis, as key metabolites in the specific response of each bacterium. Ultimately, we evaluated different abiotic and biotic stressors on plants emerging from treated seeds, finding an enhancement of the resistance of the adult plants in all cases. Moreover, plants emerging from seeds treated with B. velezensis exhibit a slowed-down program of development that does not compromise their favorable response to stressors. These findings suggest that two different plant growth and resistance developmental programs, triggered by closely related Bacillus species, may converge toward a common goal.
Keywords: Relaciones planta-microbio; Bacillus; Metabolitos secundarios; Microbioma